1978
DOI: 10.1128/aac.14.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Clavulanate Potentiation of Cephalosporin Activity Against Clinical Isolates of Cephalothin-Resistant Klebsiella pneumoniae

Abstract: Plasmid-carrying Klebsiella pneunomiae clinical isolates with agar dilution miniimum inhibitory concentrations (MIC) of 32 pg/ml or greater were tested for in vitro potentiation of cephalothin activity by clavulanic acid (BRL-14151), an inhibitor of beta-lactamases. The addition of 10 ,g of clavulanate per ml caused greater than a 500-fold reduction in geometric mean cephalothin agar dilution MIC, with lesser but significant reductions resulting from clavulanate concentrations of 5 or 1 jig/ml. Clavulanate-pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the combined antibacterial activity ofbeta-lactam antibiotics other than AMC with CVA may be found against APCresistant strains, as reported by earlier studies (6,9).…”
Section: Resultsmentioning
confidence: 54%
“…Therefore, the combined antibacterial activity ofbeta-lactam antibiotics other than AMC with CVA may be found against APCresistant strains, as reported by earlier studies (6,9).…”
Section: Resultsmentioning
confidence: 54%
“…are generally susceptible to cephalothin and most cephalosporins but are moderately resistant to penicillins by virtue of synthesis of a chromosomal penicillinase (14,20,21,27). Some Klebsiella isolates are resistant to high levels of penicillins by production of plasmid-mediated TEM-like penicillinases; these strains also have reduced susceptibility to the older cephalosporins (7,19,24). Recently, the emergence of resistance to broad-sprectrum cephalosporins has been reported in strains of Klebsiella oxytoca (6, 15) and Klebsiella pneumoniae (22).…”
mentioning
confidence: 99%
“…Although it has little inherent antibacterial activity, it protects the labile penicillins and cephalosporins from destruction by bacterial , 8-lactamase (4,6,8,9,13). In vitro studies have demonstrated that clavulanic acid possesses a very wide spectrum of inhibition (3), which results in marked enhancement of,-lactam antibiotics against many 8-lactamase-producing organisms (3,9,13) found to have infecting strains with amoxicillin MICs above 10 ug/ml were considered for enrollment in the study.…”
mentioning
confidence: 99%